Impact of macroalgal blooms on biogeochemical processes in estuarine systems: a case study in the eastern Gulf of Finland, Baltic Sea - Polyak, Yulia; Gubelit, Yulia; Bakina, Lyudmila; Shigaeva, Tatyana; Kudryavtseva, Valentina (Journal of soils and sediments, 2024)
Purpose Macroalgae blooms are particularly common in the coastal zone of the Neva Estuary situated in the eastern Gulf of Finland. Accumulation of green opportunistic algae on sediments is associated with a decrease in redox potential, changes in sediment function, and deterioration of the coastal zone. The aims of this study were to assess the role of macroalgae in the spatiotemporal distribution and activity of sediment microbial enzymes involved in biogeochemical cycles; and to evaluate biochemical indicators sensitive to macroalgae dynamics. Methods Samples of both surface sediments and macroalgae were collected at nine sites located in the coastal zone of the eastern Gulf of Finland. Sixteen sampling campaigns were performed from 2014 to 2019. Sediments were analyzed for pH, Eh, total organic carbon, ammonia–nitrogen, and phosphate content. Algal biomass and sediment enzyme activities were measured. To compare sediments at different sites according to the level of algal biomass, the geometric mean of enzyme activities (GMea) index was applied. Results The results revealed shifts in enzyme activity toward higher relative levels of dehydrogenase, catalase, phosphatase, and urease at sites subject to algal bloom. The relationships between algal biomass and enzyme activities were dependent on the seasons. The geometric mean of enzyme activities was a suitable index to incorporate the set of sediment enzyme activities in a single numerical value, which was sensitive to changes in algal biomass. The organic carbon, phosphorus, and nitrogen contents have been identified as factors potentially involved in the regulation of enzyme activity providing additional information to link the amount of macroalgae biomass during blooms, nutrient content, and metabolism of sediment microorganisms. Conclusions This enzymological study demonstrated the important role of macroalgae in the spatiotemporal distribution of sediment microbial enzymes involved in the main biogeochemical cycles. The findings of this study can provide a basis for understanding the impact of macroalgae on biogeochemical processes in sediments, which is important for the monitoring and assessment of the ecological effects of macroalgal blooms in aquatic environments.